Application of international economic sanctions by the United Nations and by the European Union - Rozēns, Heinrihs (Riga Graduate School of Law, 2023)
There are several organizations in the international environment that have the authority to apply and implement economic sanctions in order to preserve international peace and security. The United Nations and the European Union have established their dominant role in the international arena. Since both of these organizations are authorized to apply economic sanctions, a question arises on how the application as well as implementation of economic sanctions is regulated. The legal regulation behind this authority may reveal the ultimate goal embedded during the formation of these international organizations for which such authority has been assigned to them. Additionally, subsequent legal aspects arising from the legal regulation in question may provide the opportunity to compare the two organizations and establish their mutual relationship in the matter of economic sanctions and the use of them.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Economic sanctions; the United Nations; the European Union